Analiza avtomatskega sistema za spremljanje interkacij med zdravili - Šoštarić, Sabina (Farmacevtski vestnik, 2014)
Inadequate therapy often leads to adverse drug events (ADEs) which can be prevented by information technology support. The aim of this study was to analyse the results and the performance of the automated interaction check system that is implemented in the computerized physician order entry system inorder to identify current problems and shortcomings. This was investigated in a prospective (geriatric ward) and retrospective manner (hospital wide). A total of 45 ADEs were identified in 31 patients during a prospective study (6.7% of ADEs certainly, 51.1% of ADEs likely, 22.2% of ADEs possibly, and 20.0% of ADEs unlikely attributable to drug-drug interactions). Symptoms that most often occurred were falls (20.4%) and hypotension (18.5%). In the retrospective study, 2890 alerts were generated by the drug-drug interaction module and 82.1% of them were overridden. The most common alert (72.1%) was a warning for the risk of hyperkalemia. The study showed that ADEs occur frequently in the elderly and can be reduced by clinical pharmacists' interventions. An automated alert system can improve patient safety but can also cause alert fatigue if the rate of overridden alerts is too high. On the basis of retrospective and prospective studies the system was fine-tuned in such a way that alerts are appearing only when clinically relevant.
Keywords: elektronsko predpisovanje zdravil; interakcije med zdravili; retrospektivna študija; sistemi za podporo pri kliničnem odločanju; starostniki